B-site disorder induced Griffiths phase evolution and high magnetocaloric effect in La0.7Sr0.3A0.05Mn0.95O3 (A= Si, Ti). (April 2023) - Jagadish Kumar, G.; Jose, Ashika; Jinu, E.P.; Saravanan, T.T.; Senthil Kumar, E.; Navaneethan, M.; Sreemoolanadhan, H.; Kamala Bharathi, K.
Highlights: Ti doped La0.7 Sr0.3 MnO3 exhibits higher entropy change (1.08 J/kg K) at room temperature and low magnetic field. Griffiths phase arises as a result of doping either Si or Ti in Mn site. 5 mol% of Si and Ti doping at the mn site of La0.7 Sr0.3 MnO3 leads to a decrease in Curie temperature (TC ) toward room temperature. Abstract: We report on evaluation of Griffiths phase and enhanced magnetic entropy change at low magnetic fields in B-site disordered perovskite La0.7 Sr0.3 A0.05 Mn0.95 O3 ( A = Si, Ti) bulk samples. 5 mol% of Si and Ti doping at the Mn site of La0.7 Sr0.3 MnO3 leads to a decrease in Curie temperature (TC ) towards room temperature, which is observed to be 365.2 K and 314.7 K respectively. Griffiths phase arises as a result of doping either Si or Ti in Mn site. Ti doped La0.7 Sr0.3 MnO3 exhibits higher entropy change (1.08 J/kg K) than Si (0.83 J/kg K) at room temperature. The increase in magnetic entropy change and high reduction in TC towards room temperature caused by Ti doping in the La0.7 Sr0.3 MnO3 implies that these materials might be exploited for magnetic cooling in low magnetic fields near room temperature. Critical exponent analysis indicates the possibility of 3D Heisenberg spin glass like system in both compounds. Graphical abstract: Image, graphical abstract